Pengaruh Reward Dan Punishment Terhadap Kinerja Karyawan Pada Hotel Sibayak Internasional - Lase, Esterina Ningsih; Tauhid, Booni; Riady, Iwan (TEHBMJ (Tourism Economics Hospitality and Business Management Journal), 2023)
The goal of this study is to identify the rewards and punishments used at the Hotel Sibayak Internasional as well as their impact on worker productivity. A quantitative approach with descriptive investigations is the methodology adopted. The population of this study consisted of 103 totl workers, and questionnaires and interviews were used to gather data from a sample of 50 respondents and 10 informants. According to the findings of the simultaneous effect test (Test f), the combined effect of reward and punishment on performance has a significant value of 0.000<0.05. According to this, Hotel Sibayak Internasional awards and penalties for staff performance have a favourable and substantial influence concurrently and in part results from interviews show that incentive and punishment have animapact on employee performance, which is backed by quantitative data. In order to encouragestaff to pay closer attention to themselves and build the capacity for the hotel’s sustainability in the future. Hotel Sibayak Internasional can further update amd maintain the system of rewards and punishments that has been functioning successfully.